Evaluation of Non-Uniform Thermal Aging of XLPE Cable Based on Modified Debye Model - Zhang, Yiyi; Gu, Guangfeng; Liu, Jiefeng; Jiang, Fengyu; Fan, Yufan; Zha, Junwei (Frontiers in Materials, 2022)
The insulation information contained in polarization/depolarization curve (PDC) is widely used to evaluate insulation condition of the cross-linked polyethylene (XLPE) cables. However, the parameters of extended Debye model are inaccurate due to non-uniform phenomenon of cable thermal aging usually. The modified Debye model is proposed in this work to improve this condition, and the effectiveness of the revised model is confirmed by PDC tests with non-uniform and uniform aging materials. It is found that the parameters of the extended Debye model tend to overestimate the cable insulation performance, while the characteristic parameters obtained by modified Debye model can better reflect the real situation of cable non-uniform aging, and the modified Amod has a good accuracy in the evaluation of cable insulation status. This work can provide the basis and reference for XLPE cable condition evaluation in the future.